Association of tea and its extracts with colorectal adenomas: meta-analysis and systematic review - Guan, Xifei; Liu, Nawen; Zhu, Zhixin; Xu, Yanxue; Xiong, Dehai; Li, Xiuyang (Frontiers in Nutrition, 2023)
Background: There are many studies on the association of tea and its extracts with colorectal adenomas, but the results have varied. The study aims to investigate the effect of tea and its extracts on colorectal adenomas using meta analysis and systematic review. Methods: Literature was obtained through PubMed, Cochrane Library, Embase and Chinese BioMedical Literature Service System since the establishment of the database until April 31, 2023. Search terms include adenomas, polyps, colorectal, rectal, rectum, tea, epigallocatechin, drinking and beverages. Meta-regression analysis was used to infer the source of heterogeneity. Heterogeneity was assessed using I2 statistics and Q test. The effect measures were odds ratio (OR) and 95% confidence interval (95% CI). Stata17.0 software was used for data processing. Results: The findings indicated that study design, types of tea intake, occurrences, regions and grades of adenomas were statistical homogeneity. Tea and its extracts were negatively correlated with the risk of colorectal adenomas (OR=0.81, 95% CI: 0.66-0.98). No publication bias was found in this study ( and the results are robust. Conclusions: This study suggests that tea and its extracts have a certain protective effect on colorectal adenomas, which provides scientific evidence for preventive strategies for colorectal adenomas. As for the causal relationship between tea and its extracts on colorectal adenomas, further prospective studies are needed.